EQUALITY OF WOMEN IN SIKH IDEOLOGY - Kaur, Surinder (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The status of a woman in a society shows the social, cultural, religious and political scenario of that society. The position of the woman has passed many phases. It becomes evident after studying the fundamental teachings of different spiritual traditions that different religions accorded high status to the woman. Through this research paper, an effort has been made to know the status of the woman in Sikhism. For this purpose, Semitic and Aryan religious traditions have been made the foundation to understand the status of the woman prior to the emergence of Sikhism. Misogynistic interpretation of the myth of Adam and Eve in Judeo-Christian and Islamic traditions and Pursha-Prakriti duality in Hindu Sankh philosophy made it clear that it is male chauvinism and misogynistic bent of mind which undermined the role of the woman in those societies. In the fifteenth century, Guru Nanak, the founder of Sikhism and his successor Sikh Gurus accorded very high status to the woman. Guru Ram Das, fourth Nanak, composed Lavan- the recitation of which became an essential part of the Sikh marriage ceremony. Lawans helped the women to get worthy status with men not only in this world but in spiritual realm also. Women in Sikhism through the institution of marriage regained their lost status. In this research paper, it has been concluded that Eve and Prakriti i.e. women are enabled to play equal and more vibrant role in the socio-religious, political and economic spheres due to the egalitarian and humanistic message of the Sikh Gurus. Sikhism has made it possible to wipe out the gender bias and narrow-mindedness associated with a male dominated society.